Exploring Moral Values in Mahfudzhot to Enhance Students' Respect for Teachers - Al Fajar, Adam Hafidz (Jurnal Paradigma, 2024)
This study aims to explore the moral values contained in Mahfudzhot to enhance students' respect for their teachers. In the context of Islamic boarding schools (pesantren), respect for teachers is a core value that has increasingly declined due to the influence of globalization and social media. The research employs a qualitative method with a literature review approach to analyze the moral values in Mahfudzhot from various sources. The findings indicate that Mahfudzhot contains profound moral messages, such as the importance of politeness, humility, and responsibility, which are relevant for building students' character. The expressions in Mahfudzhot provide guidance on respecting teachers as guides in knowledge and morality. Unfortunately, the application of these values is often limited to rote memorization without deep comprehension, resulting in suboptimal impacts on students' character development. This study recommends integrating Mahfudzhot values contextually into the pesantren curriculum to enhance the practice of students' respect for teachers. By strengthening manners and ethics through Mahfudzhot, it is expected to foster a harmonious relationship between teachers and students, supporting the success of character education in pesantren, despite the challenges of the modern era.